(untitled) (INNOVATIVE ECONOMY, 2021)
Batiuk L.A., Kravchenko O.M. CRYPTOCURRENCY: MECHANISM OF FUNCTIONING AND PROSPECTS OF DISTRIBUTION IN THE CONDITIONS OF GLOBALIZATION Purpose. The aim of the article is deepening ideas about the place, role, tasks and mechanism of operation and prospects for the spread of cryptocurrencies as an innovative institutional form of money circulation in the context of globalization. Methodology of research. The theoretical and methodological basis of the study are the dialectical method of cognition, the conceptual provisions of economic theory, scientific works of foreign and domestic scientists on the mechanism of operation and prospects for the spread of cryptocurrencies in the context of globalization. A systematic approach to the study and timely detection of global problems of transformation of the nature of financial intermediation in the monetary system is also used. The study of economic aspects of the content of virtual digital assets (cryptocurrency) is carried out using such methods as analysis, synthesis, abstraction, generalization, scenario planning and forecasting of economic processes. Findings. A critical review of scientific developments on the content and features of the mechanism of cryptocurrencies in the economy with further outline of prospects for their spread in the context of globalization is performed. The developed theoretical and practical principles made it possible to reveal the content of transformations in the system of money circulation. The conducted research allowed to state the difference between the quasi-financial assets (digital virtual money) and traditional (fiduciary) money. Originality. The substantiation of theoretical and applied ideas about the speed and volume of distribution of virtual digital currencies in the conditions of globalization has been further developed, approaches to non-state payment support systems have been systematized. Practical value. The results of the conducted study can be the basis for further research on the spread of virtual digital currencies (cryptocurrencies), can also be used to shape the financial policy of Ukraine in the monetary system. Key words: cryptocurrency, global economy, financial intermediation, central bank, digital platforms.